2023
DOI: 10.1002/pits.22902
|View full text |Cite
|
Sign up to set email alerts
|

Positive affect, negative affect, and psychological resilience mediate the effect of self‐compassion on mental toughness: A serial mediation analysis

Abstract: Following the positive youth development perspective that emphasizes the importance of focusing on the positive assets of youth to be developed, this study examined the variables related with mental toughness, a trainable skill that is associated with psychological and academic well‐being outcomes, in preadolescent youth. The effect of self‐compassion on the mental toughness of preadolescents and the serial mediating effect of positive/negative affect and psychological resilience was explored for the first tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Higher scores indicate greater mental toughness. The MTQ48 has demonstrated high reliability and validity across various populations and settings, confirming its robustness as a measure of mental toughness in numerous studies (Ceylan, 2023;Eryilmaz et al, 2023;Rintaugu et al, 2022;Sorensen et al, 2016).…”
Section: Mental Toughnessmentioning
confidence: 71%
See 1 more Smart Citation
“…Higher scores indicate greater mental toughness. The MTQ48 has demonstrated high reliability and validity across various populations and settings, confirming its robustness as a measure of mental toughness in numerous studies (Ceylan, 2023;Eryilmaz et al, 2023;Rintaugu et al, 2022;Sorensen et al, 2016).…”
Section: Mental Toughnessmentioning
confidence: 71%
“…Responses are rated on a 5-point Likert scale from 0 (not true at all) to 4 (true nearly all the time), with higher scores indicating greater resilience. The CD-RISC has been validated in numerous studies and has shown high reliability and validity across different populations, making it a reliable tool for assessing emotional resilience (Afek et al, 2021;Darbani & Parsakia, 2023;Eryilmaz et al, 2023;Guo et al, 2023; Han E-ISSN: 3041-8542 & Wang, 2022; İme & Ümmet, 2022;Li, 2023;Liu et al, 2018;Sugawara et al, 2021).…”
Section: Emotional Resiliencementioning
confidence: 99%